I came that they may have life, and have it abundantly : the Prosperity Gospel in the South African context - Stuart, Donald (Middlebury College, 2022)
The prosperity gospel represents the confluence of these two forces in a strain of Christianity which preaches that God wants his followers to be rich. The central tenet of this teaching is that those who have enough faith are entitled to receive blessings from God which will make them prosper. Christianity is growing at incredible rates in Sub-Saharan Africa, and prosperity preaching is especially strong in this region. An incredible evangelistic tool, the prosperity gospel offers believers redemption accompanied by monetary gain. This is grace which includes a pot of gold. It is therefore unsurprising that the church is growing rapidly in this region; who would not want to join a movement that has centuries of credibility, upstanding moral principles, and now a promise of financial abundance? With the prosperity gospel, Christianity has joined the materialistic, consumer-oriented bandwagon that defines our world today.
free